2022
DOI: 10.3847/1538-4365/ac366c
|View full text |Cite
|
Sign up to set email alerts
|

Very Large Array Radio Study of a Sample of Nearby X-Ray and Optically Bright Early-type Galaxies

Abstract: Many massive early-type galaxies host central radio sources and hot X-ray atmospheres indicating the presence of radio-mechanical active galactic nucleus (AGN) feedback. The duty cycle and detailed physics of the radio-mode AGN feedback is still a matter of debate. To address these questions, we present 1–2 GHz Karl G. Jansky Very Large Array radio observations of a sample of the 42 nearest optically and X-ray brightest early-type galaxies. We detect radio emission in 41/42 galaxies. However, the galaxy withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 266 publications
1
20
1
Order By: Relevance
“…The analysis of the Low-Frequency ARray (LOFAR) DR1 images of galaxies included in the main galaxy spectroscopic sample of the Sloan Digital Survey (SDSS) led Sabater et al (2019) to the conclusion that all galaxies with a mass M > 10 11 M display radio-AGN activity with a power >10 21 W Hz −1 , that is, they are always switched on. A similar result was found by Grossová et al (2022) from their study of 42 nearby and X-raybright, early-type galaxies, all of them being detected at radio frequencies.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The analysis of the Low-Frequency ARray (LOFAR) DR1 images of galaxies included in the main galaxy spectroscopic sample of the Sloan Digital Survey (SDSS) led Sabater et al (2019) to the conclusion that all galaxies with a mass M > 10 11 M display radio-AGN activity with a power >10 21 W Hz −1 , that is, they are always switched on. A similar result was found by Grossová et al (2022) from their study of 42 nearby and X-raybright, early-type galaxies, all of them being detected at radio frequencies.…”
Section: Introductionsupporting
confidence: 86%
“…Several studies, already cited in the introduction, indicate that massive ETGs are all associated with a radio source (Brown et al 2011;Sabater et al 2019;Grossová et al 2022), suggesting that their active nuclei are always switched on. Our results confirm this observational evidence because the 25 galaxies in the present sample more luminous than M K = −25.8 are all detected in the LOFAR images.…”
Section: Comparison With Previous Studiesmentioning
confidence: 98%
“…A significant difference with respect to the study in Grossová et al (2022) is related to the radio morphology; these authors found that 67% of their galaxies are associated with extended radio sources, a higher fraction than obtained in our sample (24%). This discrepancy is reduced by considering the different criterion adopted for the definition of extended sources: in our analysis, we considered extended sources to be those in which the 3σ radio contour extends to a radius of at least 15 , ∼ 6 kpc at the median distance of the sample; Grossová et al, thanks to the higher spatial resolution of their radio images, considered all sources with a size exceeding twice the beam size as extended, which is typically ∼ 2 .…”
Section: Comparison With Previous Studiescontrasting
confidence: 98%
“…Nevertheless, the vast majority of low-redshift active galactic nuclei (AGNs) in early-type galaxies operate in the radio-mechanical (kinetic) mode, which is observed in the form of radio lobes and X-ray cavities (e.g. Fabian 2012;Shin et al 2016;Grossová et al 2022).…”
Section: Introductionmentioning
confidence: 99%